2018
DOI: 10.1371/journal.pone.0204624
|View full text |Cite
|
Sign up to set email alerts
|

Study of the interactions of bovine serum albumin with a molybdenum(II) carbonyl complex by spectroscopic and molecular simulation methods

Abstract: Therapy with inhaled carbon monoxide (CO) is being tested in human clinical trials, yet the alternative use of prodrugs, CO-Releasing Molecules (CORMs), is conceptually advantageous. These molecules are designed to release carbon monoxide in specific tissues, in response to some locally expressed stimulus, where CO can trigger a cytoprotective response. The design of such prodrugs, mostly metal carbonyl complexes, must consider their ADMET profiles, including their interaction with transport plasma proteins. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…BSA is known to interact strongly with probes containing carboxylic groups. [42][43] Consistent with this trend, the carboxylate-containing probe 3D gave up to an 85fold increase in fluorescence when bound to BSA (data not shown), but the neutral ester-containing probe 4D only showed a minimal 3-fold increase (Fig. 3C).…”
Section: Resultssupporting
confidence: 66%
“…BSA is known to interact strongly with probes containing carboxylic groups. [42][43] Consistent with this trend, the carboxylate-containing probe 3D gave up to an 85fold increase in fluorescence when bound to BSA (data not shown), but the neutral ester-containing probe 4D only showed a minimal 3-fold increase (Fig. 3C).…”
Section: Resultssupporting
confidence: 66%
“…In this context, proteins have gained increasing interest as CORM carriers due to low toxicity and stability. In the case of CORMs that are chemically stable in water or plasma, the only example studied, [Mo­(η 5 -Cp)­(CH 2 COOH)­(CO) 3 ], revealed that the interactions with carrier proteins like bovine serum albumin (BSA) are dynamic, unspecific, and dominated by hydrophobic forces . In terms of tissue specificity control, this is not advantageous and, therefore, for these nonlabile CORMs, the control of CO release must be installed on the CORM molecule like in most small-molecule drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of CORMs that are chemically stable in water or plasma, the only example studied, [Mo(η 5 -Cp)-(CH 2 COOH)(CO) 3 ], revealed that the interactions with carrier proteins like bovine serum albumin (BSA) are dynamic, unspecific, and dominated by hydrophobic forces. 33 In terms of tissue specificity control, this is not advantageous and, therefore, for these nonlabile CORMs, the control of CO release must be installed on the CORM molecule like in most small-molecule drugs. On the contrary, the interactions of the chemically labile CORM-3 with several proteins, such as human serum albumin (HSA), human transferrin, hemoglobin, myoglobin, and hen egg-white lysozyme (HEWL), are completely different and have been characterized by different experimental techniques, including X-ray crystallography, with a crystal structure of the adduct with HEWL.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, protein-CORM demonstrated both short circulation time and nontargeted distribution once they entered the body. 175 To manage these issues, CORM was conjugated to gold NPs, which extended their circulatory halflife and improved the targeted delivery and sustained release of loaded CO. The nanoformulated CORM had high cellular uptake efficacy and elicited strong anti-inflammatory effects and quick tissue regeneration in the wound area.…”
Section: Chronic Inflammationmentioning
confidence: 99%